Utilization of Molecular Markers for Rice Breeding - Tasliah, Tasliah (Jurnal AgroBiogen, 2021)
Rice is the staple food for more than half of the world's population. Rice production in 2050 must increase by at least 50% to keep up with the population growth. Efforts to increase rice production continue using various strategies. Breeders apply multiple approaches including application of molecular markers in developing varieties better than the previous ones. Since the discovery of the restriction fragment length polymorphism (RFLP) markers in 1980s and the development of polymerase chain reaction (PCR) method, many types of molecular markers have been developed and applied to various crops including rice. Various molecular approaches to map genetic loci associated with rice superior traits were conducted. The mapped loci are very useful for rice breeding purposes. This paper reports the results of mapping and breeding economically important traits in rice, mainly those related to abiotic stresses, agronomic traits, yield, and yield quality. These included characters of semidwarf stature, aromatic grain, high yield potential, eating quality, higher Zn and Fe grain, more tolerant to abiotic stresses, such as salinity, drought, phosphate deficiency, Al toxicity and Fe toxicity, submergence, as well as early maturity character. The mapped characters can be transferred using marker-assisted backcrossing (MABC) method into cultivated rice genotypes well-adopted by farmers. Several countries including Indonesia have benefited from this breeding method, and Indonesia have released several rice varieties developed through MABC. These include rice varieties such as Code, Angke, Inpari 30, Inpari Blas, Inpari HDB, Bio Patenggang Agritan, and Bioni 63 Ciherang Agritan